Recurrent laryngeal never monitoring versus non-monitoring in parathyroid surgery - Mu, Yongliang; Bian, Xuehai; Yang, Junjie; Li, Yang; Zhang, Yushuai; Dionigi, Gianlorenzo; Zhao, Yishen; Sun, Hui (Frontiers in Endocrinology, 2023)
Background Although intraoperative neural monitoring (IONM) is well established in thyroid surgery, it is less commonly analyzed in parathyroid operations. This study presents the results of IONM for primary and secondary hyperparathyroidism surgery. Methods We retrospectively assessed 270 patients with primary hyperparathyroidism (PHPT), 53 patients with secondary hyperparathyroidism (SHPT), and 300 patients with thyroid cancer from June 2010 to June 2022 in one hospital in China. The follow-up was 12 months. Demographic, electromyography data from IONM, laboratory, and clinical information were collected. Laryngoscopy was collected from 109 patients with PHPT in whom IONM was not used. All groups were assessed by Pearson’s chi-square test and Fisher’s exact probability method to verify the relationship between parathyroid size and location, duration of surgery, preoperative concordant localization, laryngeal pain, IONM outcomes, cure rate, and RLN injury. Visual analog scale (VAS) assessed laryngeal pain. RLN outcomes were measured according to nerves at risk (NAR). Results The study comprehended 918 NAR, that is 272, 105, 109, and 432 NAR for PHPT, SHPT with IONM, PHPT without IONM, and thyroid surgery control group, respectively. IONM successfully prevented RLN injury (P<0.001, P=0.012): Fifteen (5.51%) RLNs experienced altered nerve EMG profiles during surgery, and five (1.84%) experienced transient RLN injury in PHPT patients. Five (4.76%) RLNs were found to have altered EMG profiles during surgery, and one (0.95%) RLN had a transient RLN injury in SHPT patients. There was no permanent nerve injury (0.00%) in this series. There was no association between location, gland size, preoperative concordant localization, cure rate, duration of surgery, and IONM (P >0.05). Duration of surgery was associated with postoperative pharyngeal discomfort (P=0.026, P=0.024). Transient RLN injury was significantly lower in patients with PHPT who underwent IONM than in those who did not. Intraoperative neuromonitoring played an effective role in protecting the recurrent laryngeal nerve (P=0.035). Compared with parathyroidectomy, thyroidectomy had a higher rate of RLN injury (5.32%, P<0.001). Conclusion IONM for SHPT and PHPT offers rapid anatomical gland identification and RLN functional results for effective RLN protection and reduced RLN damage rates.